Local Knowledge of Pessian Women in The Management of Fhising Resources (Study on coastel women in Puger, Jember Regency) - Saputra, Aditya Eka; Indrianti, Deditiani Tri; Alkornia, Sylva (Learning Community : Jurnal Pendidikan Luar Sekolah, 2024)
The purpose of the research is to describe the local knowledge of coastal women in the management of fisheries resources (study on coastal women of Puger, Jember Regency). Local knowledge of coastal women is analyzed through the theory of ecofeminism. Meanwhile, the management of fisheries resources carried out by women can be seen from community participation and communication skills. The type of research used is descriptive with a qualitative approach. Data collection techniques through observation, interviews, and documentation. Data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results showed that coastal women's local knowledge is based on their experience from generation to generation which will cause them to be able to dominate participation in fisheries resource management. The ability of coastal women in selling their catches is based on their communication skills. In the view of ecofeminism, the involvement of coastal women must be recognized in managing and protecting nature in addition to their needs